STATE RESPONSIBILITY IN CONTROLLING CLIMATE CHANGE THROUGH CARBON ECONOMIC VALUE - Pangestu, Ilham Aji; Waluyo, Dadi; Mozin, Nopiana (Universitas Negeri Gorontalo, 2025)
The issue of climate change necessitates active state participation inmitigating greenhouse gas (GHG) emissions through the adoption ofequitable and sustainable policies. This study seeks to examine thenature of state responsibility in climate change mitigation inIndonesia, with a particular focus on the implementation of CarbonEconomic Value (NEK) as delineated in Presidential Regulation No.98 of 2021. This research constitutes a prescriptive normative legalstudy, employing a legislative approach. The findings indicate thatthe regulatory framework for Carbon Economic Value (NEK)provides a foundational structure for NEK as an environmentaleconomic instrument to facilitate the attainment of NationallyDetermined Contributions (NDCs) through various mechanisms.Nonetheless, this framework exhibits several deficiencies, includingthe legal status of carbon units, the mechanism for stateaccountability, and inadequate protection for indigenous peoplesand local communities. Consequently, the researchers advocate forthe government to fortify the legal foundation of NEC by formulatingmore detailed and integrated technical regulations and, in the longterm, to consider the development of specific legislation on carboneconomic value. These measures are anticipated to enhance theefficacy of NEC, ensure legal certainty, and achieve ecological justicefor both present and future generations.